Development of Animated Series-Based Learning Media to Stimulate Oral Expression Skills in Children Aged 5–6 Years - Jusnidar Jusnidar; Abdul Saman; Azizah Amal; Herlina Herlina; Hasmawaty Hasmawaty (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
The development of oral expression skills in early childhood requires engaging and developmentally appropriate learning media that can stimulate children’s ability to communicate ideas, thoughts, and experiences effectively. This study aims to develop animated series-based learning media to stimulate the oral expression skills of children aged 5–6 years and to examine its feasibility and effectiveness. This research employed a Research and Development approach using the 4D model, including define, design, develop, and disseminate stages. Data were collected through needs analysis, expert validation, observation, questionnaires, and field trials. The results of the needs analysis indicate that teachers require innovative and interactive media to support children’s language development, particularly in oral expression. The developed media was validated by experts and categorized as valid with minor revisions. User responses in both small- and large-scale trials show that the media is highly feasible and effective in classroom implementation. Furthermore, the effectiveness test reveals an improvement in children’s oral expression skills, including increased speaking confidence, ability to retell stories sequentially, use of varied vocabulary, and clearer articulation. These findings indicate that animated series-based learning media is effective as an innovative learning tool that enhances children’s oral expression skills and supports language development in early childhood education.